Underlying hemodynamic differences are associated with responses to tilt testing - Artur Fedorowski (Nature Portfolio, 2021)
Abstract Aim of this study was to explore whether differences in resting hemodynamic parameters may be associated with tilt test results in unexplained syncope. We analyzed age, gender, systolic (SBP), diastolic blood pressure (DBP) and heart rate (HR) by merging three large databases of patients considered likely to be of vasovagal reflex etiology, comparing patients who had tilt-induced reflex response with those who did not. Tilt-induced reflex response was defined as spontaneous symptom reproduction with characteristic hypotension and bradycardia. Relationship of demographics and baseline supine BP to tilt-test were assessed using logistic regression models. Individual records of 5236 patients (45% males; mean age: 60 ± 22 years; 32% prescribed antihypertensive therapy) were analyzed. Tilt-positive (n = 3129, 60%) vs tilt-negative patients had lower SBP (127.2 ± 17.9 vs 129.7 ± 18.0 mmHg, p < 0.001), DBP (76.2 ± 11.5 vs 77.7 ± 11.7 mmHg, p < 0.001) and HR (68.0 ± 11.5 vs 70.5 ± 12.5 bpm, p < 0.001). In multivariable analyses, tilt-test positivity was independently associated with younger age (Odds ratio (OR) per 10 years:1.04; 95% confidence interval (CI), 1.01–1.07, p = 0.014), SBP ≤ 128 mmHg (OR:1.27; 95%CI, 1.11–1.44, p < 0.001), HR ≤ 69 bpm (OR:1.32; 95%CI, 1.17–1.50, p < 0.001), and absence of hypertension (OR:1.58; 95%CI, 1.38–1.81, p < 0.001). In conclusion, among patients with suspected reflex syncope, younger age, lower blood pressure and lower heart rate are associated with positive tilt-test result.